Does natural resource extraction compromise future well-being? Norwegian Genuine Savings 1865-2018 - Johanna Fink; Cristián Ducoing (Lund University, School of Economics and Management, Lund Institute for Sustainability Impact, 2021)
Over recent years Genuine Savings (GS) has emerged as an indicator for weak sustainability and predictor of socio-economic well-being. This paper presents the first long-term GS estimates for Norway, covering the period from 1865 until 2019. The preliminary results indicate unsustainable development throughout most of the period leading up to the Second World War and sustainable development ever since 1946. This result is rather surprising since the discovery of oil and natural gas fields in 1969 resulted in substantial natural resource depletion, which is usually associated with negative levels of GS. However, in a particularity compared to most natural resource exporters, Norway managed to achieve sustainable development by compensating natural resource depletion with high investments into human and physical capital.
Keywords: N53; N54; N13; Q56; Q33; 330; Norway; Natural Resources; Genuine Savings; Oil; Well-being